Sulfide solid electrolyte, preparation method thereof, battery and application

By regulating the preparation process of sulfide solid electrolytes and optimizing the ratio of (111) to (311) crystal planes, the problem of discontinuous lithium ion migration path in sulfide solid electrolytes was solved, and high ionic conductivity and high-performance battery applications were achieved.

CN120767394AActive Publication Date: 2025-10-10GUANGZHOU TINCI MATERIALS TECH

Patent Information

Application Number
CN202511281536.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-09
Publication Date
2025-10-10
Estimated Expiration
2045-09-09

AI Technical Summary

Technical Problem

The ionic conductivity of existing sulfide solid electrolytes is difficult to meet the requirements of high power output and fast charging and discharging, mainly because the disordered crystal plane orientation in the crystal structure leads to discontinuous lithium ion migration paths, and the existing technology lacks a systematic regulation method.

Method used

By optimizing the preparation process of sulfide solid electrolyte, regulating the diffraction peak area ratio corresponding to the (111) and (311) crystal planes, and combining the control of particle size, solvent dosage and sintering temperature, a continuous lithium ion migration path is constructed.

Benefits of technology

The ionic conductivity of sulfide solid electrolytes has been significantly improved, which has enhanced the safety and energy density of batteries and is suitable for electric vertical take-off and landing aircraft.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120767394A_ABST
    Figure CN120767394A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrochemistry, and provides a sulfide solid electrolyte, a preparation method thereof, a battery and application. The chemical formula of the sulfide solid electrolyte is Li7-aPS6-aXa, X is halogen, and a is greater than or equal to 1 and less than or equal to 2; wherein the peak area of a diffraction peak corresponding to a (111) crystal plane of the sulfide solid electrolyte is I1, the peak area of a diffraction peak corresponding to a (311) crystal plane of the sulfide solid electrolyte is I2, and I1 / I2 is larger than or equal to 0.2 and smaller than or equal to 0.3. The I1 / I2 of the sulfide solid electrolyte disclosed by the invention is within the range, a good crystal structure and a relatively large interface area can be provided, and ion movement is promoted, so that relatively high ionic conductivity is obtained. Furthermore, according to the method disclosed by the invention, the high ionic conductivity of the product is ensured by reducing the solvent dosage and optimizing the sintering step, and meanwhile, the environmental pollution, the energy consumption and the production cost are remarkably reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a sulfide solid electrolyte and a preparation method thereof, a battery containing the sulfide solid electrolyte, and applications of the battery. Background Art

[0002] Solid-state electrolyte materials are a key component in achieving high-safety, high-energy-density all-solid-state lithium batteries. In recent years, sulfide-based solid electrolytes have attracted widespread attention due to their relatively high room-temperature ionic conductivity and good interfacial properties. However, the ionic conductivity of most sulfide electrolyte systems currently remains insufficient to meet the demands of practical applications such as high power output and rapid charge and discharge, hindering their widespread industrialization.

[0003] Existing research on improving the performance of sulfide solid electrolytes has mostly focused on optimizing chemical composition, adjusting doping elements, or improving sintering processes, but there is relatively little research on the crystal structure of the material, especially the fine control of the crystal plane structure. Since sulfide electrolytes have anisotropic crystal structures, there are significant differences in lithium ion conductivity in different crystal plane directions. If the crystal plane orientation distribution is disordered, the ion migration channels inside the material will be non-uniformly distributed, or even blocked, which will seriously affect the effective diffusion path of lithium ions and lead to low overall conductivity. However, existing technologies still lack systematic control methods for the crystal orientation of electrolyte materials. Most preparation strategies are still at the stage of disordered dense sintering, making it difficult to achieve directional construction of the crystal structure. Summary of the Invention

[0004] The purpose of this application is to provide a sulfide solid electrolyte and its preparation method, a battery containing the sulfide solid electrolyte, and the application of the battery, which can accurately control the proportion of target crystal planes during the formation of the sulfide solid electrolyte, thereby constructing a continuous, low-impedance lithium ion migration path, thereby significantly improving the ionic conductivity of the sulfide solid electrolyte material, and providing key support for the development of high-performance all-solid-state batteries. The specific technical solution is as follows:

[0005] The first aspect of the present application provides a sulfide solid electrolyte, the chemical formula of which is Li 7-a PS 6-a X a , X is a halogen, 1≤a≤2; wherein, the peak area of ​​the diffraction peak corresponding to the (111) crystal plane of the sulfide solid electrolyte is I1, the peak area of ​​the diffraction peak corresponding to the (311) crystal plane of the sulfide solid electrolyte is I2, and I1 and I2 satisfy: 0.2≤I1 / I2≤0.3.

[0006] In one embodiment of the present application, the half-width of the diffraction peak corresponding to the (111) crystal plane of the sulfide solid electrolyte is x1, and the half-width of the diffraction peak corresponding to the (311) crystal plane of the sulfide solid electrolyte is x2, and x1 and x2 satisfy: 0.12<x1<0.2, 0.14<x2<0.22.

[0007] In one embodiment of the present application, the particle size of the sulfide solid electrolyte satisfies: 0.5µm<D50<1µm, 1.4µm<D90<2µm, 10µm<D MAX <15µm.

[0008] In one embodiment of the present application, the ionic conductivity of the sulfide solid electrolyte is ≥5.3 mS / cm.

[0009] In one embodiment of the present application, the sulfide solid electrolyte further includes at least one of O, Se, F, Mg, Ca, Sr, Zn, Sc, Sb, Si, Ge, Sn, B, Al, Ga, In, Ti, Zr, V, Nb, Cu, Ni, Mn, Cr, Ag, La, Ce, Tb, Te, Pb, As, Bi, Fe, Mo, Hf, Y and Ru elements, and the elements are introduced by doping or coating.

[0010] In one embodiment of the present application, the surface of the sulfide solid electrolyte is coated with an inert oxide layer, and the inert oxide layer is selected from at least one of Li2O, Al2O3, V2O5, ZnO, ZrO2, TiO2, MgO, RuO2, La2O3, CeO2, HfO2, Y2O3, SiO2, B2O3, CuO, NbO2, LiNbO3, and LiAlO2.

[0011] The second aspect of the present application provides a method for preparing the sulfide solid electrolyte provided in the first aspect of the present application, which comprises:

[0012] Under inert atmosphere protection, a substrate and a solvent are mixed and mechanically stirred to obtain a solid mixture; wherein the substrate comprises Li2S, P2S5, and LiX, where X is a halogen; before mixing the substrate and the solvent, the substrate and the solvent are respectively crushed to 3 μm ≤ D50 ≤ 10 μm; the molar ratio of the Li2S to the P2S5 is (3-5):1; the molar ratio of the P2S5 to the LiX is 1:(2-4); and the mass ratio of the solvent to the substrate is 1:(1.5-3);

[0013] The solid mixture is allowed to stand at room temperature and pressure to evaporate the solvent, thereby obtaining a solid electrolyte precursor mixture;

[0014] The solid electrolyte precursor mixture is sintered to obtain a sulfide solid electrolyte; wherein the sintering includes a first sintering and a second sintering, the temperature of the first sintering is 150~300℃, and the time is 1~6h; the temperature of the second sintering is 450~600℃, and the time is 10~15h.

[0015] In one embodiment of the present application, the substrate and the solvent are respectively crushed to 5µm≤D50≤8µm before being mixed.

[0016] In one embodiment of the present application, the temperature of the first sintering is 200-300° C., and the time is 3-6 hours; the temperature of the second sintering is 550-600° C., and the time is 10-13 hours.

[0017] In one embodiment of the present application, the heating rate of the first sintering is 2-5°C / min; the heating rate of the second sintering is 5-10°C / min.

[0018] In one embodiment of the present application, the solvent is selected from at least one of n-hexane, benzene, toluene, cyclohexane, n-pentane, cyclopentane and dimethyl carbonate.

[0019] In one embodiment of the present application, the mechanical stirring is performed at room temperature and pressure, the rotation speed of the mechanical stirring is 300 rpm to 600 rpm, and the time of the mechanical stirring is 10 to 50 min.

[0020] In one embodiment of the present application, the solvent volatilization rate is 1.5~7.0 mg / cm 2 ·h.

[0021] In one embodiment of the present application, post-processing is required after the sintering, and the post-processing includes crushing.

[0022] The third aspect of the present application provides a battery comprising a positive electrode sheet, a negative electrode sheet, and the sulfide solid electrolyte described in the first aspect of the present application or the sulfide solid electrolyte prepared by the preparation method described in the second aspect of the present application.

[0023] The fourth aspect of the present application provides the use of the battery described in the third aspect of the present application in an electric vertical take-off and landing aircraft.

[0024] Beneficial effects of this application:

[0025] The present application provides a sulfide solid electrolyte and its preparation method, battery and application. The chemical formula of the sulfide solid electrolyte is Li 7-a PS 6-a X a, X is a halogen, 1≤a≤2; wherein, the peak area of ​​the diffraction peak corresponding to the (111) crystal plane of the sulfide solid electrolyte is I1, and the peak area of ​​the diffraction peak corresponding to the (311) crystal plane of the sulfide solid electrolyte is I2, and I1 and I2 satisfy: 0.2≤I1 / I2≤0.3. The problem of disordered crystal orientation is common in existing sulfide solid electrolytes. In particular, under uncontrolled synthesis conditions, the proportion of each crystal plane inside the grain is uneven, resulting in discontinuous lithium ion migration path or the presence of high-energy barriers, thereby limiting the improvement of the ionic conductivity of the sulfide solid electrolyte. In response to this technical problem, the present application optimizes the synthesis process conditions and regulates the ratio of the diffraction peak area corresponding to the (111) crystal plane and the (311) crystal plane in the sulfide solid electrolyte, thereby achieving the optimization of crystal orientation and improving the lithium ion migration path inside it. Specifically, the (311) crystal plane has a low migration barrier, and appropriately increasing its ratio is conducive to constructing more continuous and low-resistance ion conduction channels, thereby improving overall ionic conductivity. Meanwhile, the (111) crystal plane has certain advantages in structural stability, which helps maintain the mechanical strength and sintering density of the sulfide solid electrolyte. By controlling the crystal plane ratio within the range of this application (0.2≤I1 / I2≤0.3), the ionic conductivity is improved while ensuring the structural stability of the sulfide solid electrolyte.

[0026] Furthermore, the preparation method of the present application, by reducing the amount of solvent used, not only reduces production costs and environmental impact, but also simplifies the subsequent drying process, thereby improving overall production efficiency. By controlling the sintering temperature and time, the ionic conductivity and phase purity of the electrolyte are improved, and the overall performance of the electrolyte is enhanced. Furthermore, batteries containing the sulfide solid electrolyte of the present application or the sulfide solid electrolyte prepared by the preparation method of the present application have high safety and energy density as well as good low-temperature performance, and can be used in electric vertical take-off and landing aircraft, such as low-altitude, economical manned electric vertical take-off and landing aircraft.

[0027] Of course, it is not necessary to achieve all the advantages described above at the same time when implementing any product or method of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other embodiments can also be obtained based on these drawings.

[0029] Figure 1 This is the X-ray diffraction pattern of the sulfide solid electrolyte (Li6PS5Cl) prepared in Example 1-1;

[0030] Figure 2 The sulfide solid electrolyte (Li 5.5 PS 4.5 Cl 1.5 )’s X-ray diffraction pattern;

[0031] Figure 3 The X-ray diffraction pattern of the sulfide solid electrolyte (Li6PS5Cl) prepared in Example 2-7;

[0032] Figure 4 for Figure 1 A magnified image of the diffraction peak corresponding to the (111) crystal plane;

[0033] Figure 5 for Figure 1 A magnified image of the diffraction peak corresponding to the (311) crystal plane;

[0034] Figure 6 is the X-ray diffraction pattern of the solid electrolyte precursor mixture of Example 1-1;

[0035] Figure 7 This is the X-ray diffraction pattern of the electrolyte precursor powder of Comparative Example 5-1. DETAILED DESCRIPTION

[0036] The following will be combined with the embodiments of the present application and the accompanying drawings to clearly and completely describe the technical solutions in this application. Obviously, the embodiments described are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on this application are within the scope of protection of this application.

[0037] The first aspect of the present application provides a sulfide solid electrolyte, the chemical formula of which is Li 7-a PS 6-a X a , X is a halogen, 1≤a≤2; wherein, the peak area of ​​the diffraction peak corresponding to the (111) crystal plane of the sulfide solid electrolyte is I1, and the peak area of ​​the diffraction peak corresponding to the (311) crystal plane of the sulfide solid electrolyte is I2, and I1 and I2 satisfy: 0.2≤I1 / I2≤0.3. The inventors have found that in the sulfide solid electrolyte, the (111) crystal plane is a low-index plane with a relatively dense structure, which can effectively suppress the disordered expansion of defects and vacancies in the crystal; while the (311) crystal plane is a high-index plane with a large surface energy and abundant diffusion channels, which is conducive to the migration of lithium ions. By regulating I1 / I2 within the scope of this application, a uniform and continuous ion diffusion path can be formed in the sulfide solid electrolyte, while suppressing the formation of excessive grain boundary resistance or non-conducting areas, thereby facilitating the improvement of the ionic conductivity of the sulfide solid electrolyte.

[0038] When the I1 / I2 ratio is too low (<0.2), the proportion of high-index planes in the sulfide solid electrolyte is too high, which may cause the surface of the crystal particles to be too loose and the interface stability to decrease, thereby introducing more grain boundary defects or secondary phase deposition, which is not conducive to the continuity of ion migration; and when the I1 / I2 ratio is too high (>0.3), the proportion of low-index planes is too large. Although it can improve the crystal density, due to the limited number of diffusion channels of the (111) crystal plane itself, it actually inhibits the effective migration of lithium ions.

[0039] By optimizing the preparation process of sulfide solid electrolytes, this application successfully achieved controllable regulation of the relative ratio of (111) crystal planes to (311) crystal planes in the material, thereby improving the continuity of the ion migration path and enhancing the ionic conductivity of the sulfide solid electrolyte. Through XRD testing, it was found that under different process conditions, the diffraction peak area ratio of the (111) crystal plane to the (311) crystal plane in the sample changed significantly. Experiments have shown that when the ratio is in the range of 0.2–0.3, the material exhibits the best ionic conductivity and structural density. Combined with the preparation process, the inventors found that the following factors have a significant impact on the crystal plane ratio:

[0040] (1) Substrate particle size: Regulating the substrate particle size D50 within the range of this application (3–10 μm) is beneficial to the uniform diffusion of the reaction and the distribution of crystal nuclei, thereby providing a good foundation for directional crystal growth. A particle size that is too large may cause local concentration unevenness, induce the formation of non-ideal (311) crystal planes, and result in an I1 / I2 ratio of less than 0.2. A particle size that is too small may cause particle agglomeration during sintering, resulting in an imbalance in the crystal plane ratio and an excessively high I1 / I2 ratio.

[0041] (2) Solvent type and dosage: Using a low-polarity, inert solvent within the scope of this application can inhibit the directional complexation reaction between substrates, favoring the preferential growth of the (111) crystal plane, and making the I1 / I2 ratio within the scope of this application. Controlling the mass ratio of solvent to substrate within the scope of this application will result in a more uniform dispersion of substrate particles, which helps control the nucleation position and thus affect the direction of crystal growth; however, excessive solvent dosage can easily lead to disordered crystal plane structure, making the I1 / I2 ratio greater than 0.3.

[0042] (3) Second sintering temperature and time: The second sintering determines the directionality of grain growth. Sintering temperatures within the range of this application (450-600°C) can guide the crystals to continue growing along the low-energy plane (111), thereby increasing the proportion of (111) crystal planes and keeping the I1 / I2 ratio within the range of this application. If the temperature is too high or the holding time is too long, the system tends to a thermodynamic equilibrium state, and the high-index crystal plane (311) is prone to re-precipitation, resulting in a decrease in the crystal plane proportion and an I1 / I2 ratio of less than 0.2.

[0043] In addition, the formation of the crystal plane structure is not only affected by a single process parameter, but also by the interaction between multiple parameters. A reasonable combination of parameters is crucial to achieving the ideal (111) / (311) crystal plane ratio:

[0044] (1) There is a synergistic relationship between the mass ratio of solvent to substrate and the second sintering temperature. Under the condition of moderate solvent dosage, a lower sintering temperature easily forms a well-oriented (111) crystal plane, making the I1 / I2 ratio within the range of this application; however, if the solvent is insufficient and the temperature is increased, there is a lack of effective restriction during the crystal growth process, which easily promotes the abnormal exposure of the high-energy plane (311), resulting in an imbalance in the crystal plane ratio and an I1 / I2 ratio of less than 0.2.

[0045] (2) There is a synergistic effect between the second sintering conditions and the substrate particle size. When the substrate particle size is small (D50 is close to the lower limit), the grains have higher reactivity and larger specific surface area. At this time, if a higher second-step sintering temperature is used or the holding time is extended, it is easy to cause the grains to grow rapidly, the preferred growth direction of the crystal plane in the local area is out of control, and the (111) crystal plane ratio is induced to increase. Under the same sintering conditions, if the substrate particle size is moderate (such as D50 is in the medium range), the grain growth process is more controllable, which is conducive to maintaining a suitable (311) crystal plane ratio. Therefore, the fine particle system is more suitable for sintering parameters with medium temperature and time to avoid imbalance in the crystal plane structure and keep the I1 / I2 ratio within the range of this application.

[0046] (3) There is a synergistic relationship between the substrate particle size and the amount of solvent used. Substrates with smaller particle sizes have higher surface energy and a stronger tendency to agglomerate. If the amount of solvent used is insufficient, it is easy to cause uneven mixing and poor dispersion, which in turn leads to local orientation anomalies, affecting the uniformity of the crystal structure and increasing the probability of the formation of the (311) crystal face. On the contrary, appropriately increasing the amount of solvent used can effectively alleviate the agglomeration of fine particles, improve mixing uniformity, promote uniform contact of the reactant interface, and thus provide a basis for the subsequent orderly growth of the crystal face. For raw materials with larger particle sizes, if the amount of solvent used is too much, it may cause reaction dilution and a decrease in nucleation density, which is not conducive to the formation of a stable (111) crystal face ratio. Therefore, in practical applications, it is necessary to select an appropriate solvent ratio in combination with the raw material particle size to achieve synergistic regulation of the crystal face structure so that the I1 / I2 ratio is within the scope of this application.

[0047] Therefore, the application establishes a set of sulfide solid electrolyte preparation process systems that can be used to accurately control the crystal face ratio by the combined design and mutual matching of multiple key process parameters (including solvent usage, sintering temperature and time, substrate particle size, etc.). The system can avoid the instability factors brought by single parameter adjustment, and achieve the consistency of the crystal face orientation and the optimization of the electrochemical performance of the final sulfide solid electrolyte product. By adjusting the above process parameters, the peak area ratio I1 / I2 of the diffraction peaks corresponding to the (111) / (311) crystal faces in the XRD pattern of the product is kept in the interval of 0.2-0.3, so as to improve the ion conductivity and overall performance of the sulfide solid electrolyte, and meet the use requirements of high-performance all-solid-state battery materials.

[0048] In the application, the (311) crystal face of the sulfide solid electrolyte corresponds to a diffraction peak at 2θ = 30.3±0.5°; and the (111) crystal face of the sulfide solid electrolyte corresponds to a diffraction peak at 2θ = 15.8±0.5°.

[0049] In an embodiment of the application, the half-peak width of the diffraction peak corresponding to the (111) crystal face of the sulfide solid electrolyte is x1, and the half-peak width of the diffraction peak corresponding to the (311) crystal face of the sulfide solid electrolyte is x2, x1 and x2 satisfy: 0.12 < x1 < 0.2, 0.14 < x2 < 0.22. The x1 and x2 of the sulfide solid electrolyte of the application are in the above range, so that the sulfide solid electrolyte has high ion conductivity.

[0050] In an embodiment of the application, the particle size of the sulfide solid electrolyte satisfies: 0.5µm < D50 < 1µm, 1.4µm < D90 < 2µm, 10µm < D MAX < 15µm. The particle size D50, D90 and D MAX In the above range, the sulfide solid electrolyte has good processing performance.

[0051] In an embodiment of the application, the ion conductivity of the sulfide solid electrolyte is ≥5.3mS / cm. The inventors found in the research that the sulfide solid electrolyte of the application has high ion conductivity, and can improve the safety performance, energy density and low-temperature performance of the battery when applied to the battery.

[0052] In one embodiment of the present application, the sulfide solid electrolyte further includes at least one of O, Se, F, Mg, Ca, Sr, Zn, Sc, Sb, Si, Ge, Sn, B, Al, Ga, In, Ti, Zr, V, Nb, Cu, Ni, Mn, Cr, Ag, La, Ce, Tb, Te, Pb, As, Bi, Fe, Mo, Hf, Y and Ru elements, and the elements are introduced by doping or coating.

[0053] In the present application, the above-mentioned doping method includes but is not limited to introducing doping elements during the substrate and solvent mixing stage or introducing doping elements with a sintering aid during the sintering stage; the above-mentioned coating method includes but is not limited to forming a coating layer containing doping elements on the surface of the sulfide solid electrolyte by ball milling, vapor deposition or atomic spraying.

[0054] In one embodiment of the present application, the surface of the sulfide solid electrolyte is coated with an inert oxide layer, and the inert oxide layer is selected from at least one of Li2O, Al2O3, V2O5, ZnO, ZrO2, TiO2, MgO, RuO2, La2O3, CeO2, HfO2, Y2O3, SiO2, B2O3, CuO, NbO2, LiNbO3, and LiAlO2. The sulfide solid electrolyte with an inert oxide layer coated on the surface can effectively improve the interface stability and air stability of the solid electrolyte. The sulfide solid electrolyte with an inert oxide layer coated on the surface is prepared by the above-mentioned coating method. For example, under an inert atmosphere, the sulfide solid electrolyte Li 7-a PS 6-a X a Mixed with at least one of the above-mentioned inert oxides, then sealed and ball-milled to obtain a sulfide solid electrolyte with an inert oxide layer on the surface. 7-a PS 6-a X a The mass ratio of the inert oxide can be 95:5 to 99.99:0.01.

[0055] The second aspect of the present application provides a method for preparing the sulfide solid electrolyte provided in the first aspect of the present application, which comprises:

[0056] Under inert atmosphere protection, a substrate and a solvent are mixed and mechanically stirred to obtain a solid mixture; wherein the substrate comprises Li2S, P2S5 and LiX, where X is a halogen; before being mixed with the solvent, the substrate and the solvent are respectively crushed to 3μm≤D50≤10μm, preferably 5µm≤D50≤8µm; the molar ratio of the Li2S to the P2S5 is (3-5):1; the molar ratio of the P2S5 to the LiX is 1:(2-4); and the mass ratio of the solvent to the substrate is 1:(1.5-3). For example, before mixing the substrate with the solvent, they can be pulverized to a D50 of 3µm, 4µm, 5µm, 6µm, 7µm, 8µm, 9µm, 10µm, or a range consisting of any two values ​​therein; the molar ratio of the Li2S to the P2S5 can be 3:1, 4:1, 5:1, or a range consisting of any two values ​​therein; the molar ratio of the P2S5 to the LiX can be 1:2, 1:3, 1:4, or a range consisting of any two values ​​therein; the mass ratio of the solvent to the substrate can be 1:1.5, 1:2, 1:3, or a range consisting of any two groups of values ​​therein. The molar ratio between the substrates is limited to the above range, which can avoid changes in the material structure and the resulting decrease in ionic conductivity; the mass ratio of the solvent to the substrate is limited to the above range, which not only reduces production costs but also reduces environmental pollution compared to the traditional liquid phase method; at the same time, by reducing the amount of solvent used, the drying step does not require vacuum drying, but can be completed by standing at room temperature and pressure, which not only reduces energy consumption but also reduces production costs. Since the amount of solvent used in wet mixing is small and the stirring time is short, it is necessary to pre-treat the substrate so that its D50 is ≤10µm, which can achieve better dispersion during the wet mixing process, thereby achieving a more uniform and complete reaction during sintering, improving product uniformity and ionic conductivity; if the particle size is less than 3μm, the specific surface area of ​​the substrate powder is significantly increased, and it is easy to agglomerate during sintering, resulting in uneven particle growth and increased structural defects. Moreover, excessive pulverization may destroy the crystal structure of the substrate itself, causing deterioration of the raw material.

[0057] The amount of solvent used during wet mixing plays a role in wetting and mixing with the substrate. An appropriate amount of solvent allows for full microscopic contact and uniform mixing of the components, contributing to the formation of uniformly oriented crystal nuclei. Conversely, insufficient solvent can lead to particle agglomeration, resulting in uneven distribution of localized crystal faces or preferential growth of non-ideal crystal faces, which in turn affects the precision of controlling the I1 / I2 ratio in the final sulfide solid electrolyte product.

[0058] Specifically, the lithium sulfide (Li2S), phosphorus pentasulfide (P2S5), and lithium halides (such as LiCl and LiBr) used are each ground to a particle size distribution (D50) of 3–10 μm. This particle size distribution is significantly different from that of conventional commercially available raw materials, representing an unconventional particle size design. Commercially available lithium sulfide is often supplied in granular or agglomerated form, with a typical market particle size of 50–200 μm. Commercially available phosphorus pentasulfide, on the other hand, is primarily supplied in a distinct flake or block structure, with industrial-grade particle sizes often exceeding 100 μm. These large particle sizes also lead to uneven stacking, making it difficult to form a uniform mixing system. Furthermore, commercially available lithium halides such as LiCl and LiBr are often present as large particles or crystalline powders, with particle sizes generally exceeding 100 μm. These particles are prone to moisture absorption and agglomeration, further impacting dispersion uniformity and reactivity. Controlling the D50 of the substrate within the range of this application facilitates uniform diffusion and nucleation distribution, thus providing a favorable foundation for directional crystal growth and improving the ionic conductivity of the sulfide solid electrolyte.

[0059] The solid mixture is allowed to stand at room temperature and pressure to allow the solvent to evaporate, thereby obtaining a solid electrolyte precursor mixture. The preparation method of the present application selects standing drying at room temperature and pressure. Compared with other drying methods such as heating and vacuum drying, it can reduce the large amount of solvent that evaporates simultaneously in the mixture to form cavities, thereby further improving the ionic conductivity and overall performance of the electrolyte.

[0060] The solid electrolyte precursor mixture is sintered to obtain a sulfide solid electrolyte; wherein the sintering includes a first sintering and a second sintering, the temperature of the first sintering is 150~300℃, and the time is 1~6h; preferably, the temperature is 200~300℃, and the time is 3~6h; the temperature of the second sintering is 450~600℃, and the time is 10~15h; preferably, the temperature is 550~600℃, and the time is 10~13h. For example, the temperature of the first sintering can be 150°C, 200°C, 250°C, 300°C or a range consisting of any two of the values ​​therein, and the time can be 1h, 2h, 3h, 4h, 5h, 6h or a range consisting of any two of the values ​​therein; the temperature of the second sintering is 450°C, 500°C, 550°C, 600°C or a range consisting of any two of the values ​​therein, and the time can be 10h, 11h, 12h, 13h, 14h, 15h or a range consisting of any two of the values ​​therein. The inventors discovered in their research that the substrate begins to react during the second sintering. When the second sintering time or sintering temperature is lower than the range of this application, the substrate does not react completely, suitable crystal planes are not formed, and I1 / I2 is large, resulting in low ionic conductivity. When the second sintering time or sintering temperature is higher than the range of this application, the product sulfide solid electrolyte (LPSC) undergoes side reactions, resulting in the precipitation of LiX (such as LiCl), I1 / I2 decreases, and the overall structure of the product is destroyed, resulting in a decrease in ionic conductivity. At the same time, the sintering method of this application avoids the complicated reduced pressure drying process, directly completes the residual solvent drying and sintering process, reduces equipment requirements and energy consumption, and improves the ionic conductivity and overall performance of the electrolyte by controlling the sintering temperature and time.

[0061] The sintering temperature determines the driving force of crystal growth and the rate of particle rearrangement. By controlling the second sintering temperature within the range of this application, volatile elements such as lithium, sulfur, and halogens can be stably present, which is conducive to the controlled growth of grains between various crystal planes and promotes the formation of a reasonable ratio of (111) and (311) crystal planes. However, too high a temperature will accelerate crystal plane reconstruction, induce non-uniform growth, or cause crystal plane collapse, resulting in an imbalance in the crystal plane ratio; while too low a temperature may hinder the complete formation of crystals, resulting in insufficient selective growth of crystal planes and affecting the construction of ion migration channels.

[0062] The second sintering time affects the full growth of grains and the stability of crystal plane orientation. Short sintering time may result in incomplete grain maturity and the crystal plane ratio deviating from the target range; too long a sintering time may cause grain coarsening or accumulation of structural defects, increasing grain boundary resistance. Experimental results show that by controlling the mass ratio of solvent to substrate, the sintering temperature and sintering time of the second sintering within the range of this application, the peak area ratio I1 / I2 of the diffraction peaks corresponding to the (111) and (311) crystal planes in the sulfide solid electrolyte can be stably maintained between 0.2–0.3, thereby achieving synergistic optimization of high ionic conductivity.

[0063] In one embodiment of the present application, the heating rate of the first sintering is 2~5℃ / min; the heating rate of the second sintering is 5~10℃ / min. For example, the heating rate of the first sintering can be 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, or a range consisting of any two values ​​therein; the heating rate of the second sintering can be 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, 10℃ / min, or a range consisting of any two values ​​therein. The heating rates of the two sinterings in the present application are limited to the above range, so that the volatilization of the solvent does not introduce too many voids in the sulfide solid electrolyte, and the crystal structure of the sulfide solid electrolyte is complete and the ionic conductivity is high.

[0064] The purpose of the first sintering is to remove residual solvent from the system while preventing the rapid evaporation of the solvent from introducing large cavities into the product. The heating rate should be maintained at 2-5°C / min. Excessively high heating rates can cause the solvent to evaporate too quickly, introducing cavities. Excessively low heating rates can result in prolonged heating times, increasing work hours and energy consumption. The purpose of the second sintering is to form the argyrodite crystal form, thereby obtaining a sulfide product with high ionic conductivity. The heating rate should be maintained at 5-10°C / min. Excessively high heating rates can damage the heating equipment and cause runaway temperatures, leading to uneven heating temperatures. A heating rate lower than this will cause some phosphorus pentasulfide to decompose before the raw materials begin to react and form the target crystal form, producing gases that cannot be absorbed by the final product, resulting in a product with the appropriate elemental ratio.

[0065] In this application, there is no particular limitation on the method of controlling the heating rate, as long as the purpose of this application can be achieved. For example, the heating rate can be set by the heating program of the sintering furnace. This application does not particularly limit the selection of the sintering furnace. For example, a tubular furnace with model NBD-T1500-100T2GF can be selected.

[0066] In the present application, the inert atmosphere is not particularly limited as long as it can achieve the purpose of the present application. For example, the inert atmosphere is selected from but not limited to at least one of argon and nitrogen.

[0067] In the present application, the halogen is at least one of Cl, Br and I.

[0068] In the present application, there is no particular limitation on the conditions for allowing the solid mixture to stand, as long as the purpose of the present application can be achieved. For example, under the protection of an inert atmosphere, the mixture is allowed to stand overnight at room temperature and normal pressure to allow the solvent to evaporate and the residual solvent content to be maintained below 5 wt%.

[0069] In one embodiment of the present application, the solvent is selected from solvents that do not react with the substrate; preferably, the solvent is selected from at least one of n-hexane, benzene, toluene, cyclohexane, n-pentane, cyclopentane and dimethyl carbonate. The inventors found in their research that by using the solvent of the present application, the substrates interact better and exhibit a more moderate I1 / I2, thereby the ionic conductivity of the sulfide solid electrolyte is higher. At the same time, it can also avoid the hydrolysis of the precursor and reduce the content of oxygen impurities (such as Li3PO4) in the electrolyte, thereby improving the purity and ionic conductivity of the electrolyte. The use of low-polarity, inert solvents can inhibit the directional complexation reaction between substrates and is conducive to the preferential growth of the (111) crystal plane. By controlling the mass ratio of the solvent to the substrate within the range of the present application, the substrate particles are more evenly dispersed, which helps to control the nucleation position and thus affect the direction of crystal growth; however, excessive use can easily lead to disordered crystal plane structure.

[0070] In one embodiment of the present application, mechanical stirring is carried out at room temperature and pressure, the speed of mechanical stirring is 300 rpm to 600 rpm, and the time of mechanical stirring is 10 to 50 min. For example, the speed of mechanical stirring can be 300 rpm, 350 rpm, 400 rpm, 480 rpm, 520 rpm, 600 rpm, or a range consisting of any two values ​​therein; the time of stirring can be 10 min, 20 min, 30 min, 40 min, 50 min, or a range consisting of any two values ​​therein. By regulating the mixing method of the substrate and the solvent, the temperature, pressure, and speed of mechanical stirring within the above range, it is possible to avoid reactions between the substrates during stirring, ensuring that the substrates undergo sufficient and uniform solid-phase reactions during the sintering stage, which is beneficial to the preparation of sulfide solid electrolytes and obtaining a suitable ratio of (111) crystal planes to (311) crystal planes. When other mixing methods (such as ultrasonic dispersion, etc.), mechanical stirring under high temperature and high pressure, or too high a speed (for example, greater than 600 rpm) are used, reactions may occur between the substrates, resulting in uneven reactions in the subsequent preparation of sulfide solid electrolytes, destroying the orderly growth of crystals, and disordering the crystal plane orientation distribution in the product, especially causing the ratio of (111) crystal planes to (311) crystal planes to deviate from the expected range, affecting the ionic conductivity of the sulfide solid electrolyte. In addition, the stirring time of this application is limited to the above range, which can make the substrate contact more sufficient, thereby obtaining higher ionic conductivity. In short, the method of regulating the mixing of the substrate and the solvent is mechanical stirring, and regulating the mechanical stirring conditions within the above range can optimize the crystal orientation, improve the lithium ion migration path inside the sulfide solid electrolyte, and thus improve its ionic conductivity.

[0071] In one embodiment of the present application, the solvent evaporation rate is 1.5-7.0 mg / cm 2 For example, the solvent evaporation rate can be 1.5 mg / cm 2 h, 3 mg / cm 2 h, 4.5 mg / cm 2 h, 6 mg / cm 2 h, 7.0 mg / cm 2 h can be a range consisting of any two of these values. The inventors have found that limiting the solvent volatilization rate of the present application to the above range can prevent a large amount of solvent from volatilizing simultaneously to form cavities in the mixture, thereby further improving the ionic conductivity and overall performance of the electrolyte.

[0072] The present application does not impose any particular restrictions on the method for controlling the solvent evaporation rate, as long as the purpose of the present application can be achieved. For example, at room temperature and normal pressure, by using different evaporation containers, the thickness of the solid electrolyte precursor mixture can be controlled to be 1-5 mm, and the dry specific surface area per gram of the solid electrolyte precursor mixture can be controlled to be 1.5-3 cm 2 , in order to control the rate of solvent evaporation, the thickness and specific surface area can be obtained by measuring from the outside of the container.

[0073] In the present application, after the solid electrolyte precursor mixture is volatilized for t hours, the masses m0 and m1 of the solid electrolyte precursor mixture before and after volatilization are determined by weighing. m0 minus m1 is the amount of solvent volatilized during the volatilization time. After dividing by the volatilization time t and the dry specific surface area S, the volatilization rate v of the solvent can be obtained, v=(m0-m1) / (t×S).

[0074] In summary, by crushing the substrates separately, controlling the D50 of the substrates, using an inert solvent within the scope of this application, and regulating the stirring speed and stirring time when mixing the substrate and the solvent, the substrate can be controlled not to react before the first sintering. If the substrate partially reacts before sintering, it is easy to cause non-uniformity in the reaction process, destroy the orderly growth of the crystals, and make the crystal plane orientation distribution in the product disordered, especially causing the ratio of (111) crystal plane to (311) crystal plane to deviate from the expected range. If the substrate does not react prematurely before sintering, the solid-phase reaction in the sintering stage can be carried out under controlled conditions, which can control the nucleation and growth path of the crystals, thereby facilitating the regulation of the ratio of the diffraction peak area corresponding to the (111) crystal plane and the (311) crystal plane in the sulfide solid electrolyte within the scope of this application, thereby improving the ionic conductivity.

[0075] In one embodiment of the present application, post-processing is required after sintering, and the post-processing includes pulverization. The present application does not specifically limit the specific implementation method of pulverization, as long as it can achieve the purpose of the present application. For example, pulverization can be carried out by grinding, mechanical pulverization, and high-energy ball milling.

[0076] The third aspect of the present application provides a battery comprising a positive electrode sheet, a negative electrode sheet, and the sulfide solid electrolyte described in the first aspect of the present application or the sulfide solid electrolyte prepared by the preparation method described in the second aspect of the present application. Application of the sulfide solid electrolyte described in the present application or the sulfide solid electrolyte prepared by the preparation method of the present application in the battery significantly improves the battery's safety, energy density, and low-temperature performance.

[0077] This application does not impose any special restrictions on the positive electrode sheet and the negative electrode sheet in the battery, as long as they can achieve the purpose of this application.

[0078] The fourth aspect of the present application provides the application of the battery described in the third aspect of the present application in an electric vertical take-off and landing aircraft, especially in a low-altitude economical manned electric vertical take-off and landing aircraft, which can improve the flight endurance, safety performance and extreme environment resistance of the spacecraft. At the same time, the long-life battery can reduce the maintenance frequency and cost of the aircraft.

[0079] Example

[0080] The following examples and comparative examples further illustrate the embodiments of the present application. Various tests and evaluations were performed according to the following methods. Unless otherwise specified, "parts" and "%" are by mass, "room temperature" is 25±5°C, "normal pressure" is 101 kPa, and "overnight" refers to 12 to 24 hours.

[0081] Test methods and equipment:

[0082] Ionic conductivity test

[0083] In an argon-filled glove box, 100 mg of solid electrolyte powder was weighed and placed in a mold battery (Wuhan Chuangneng CN-01) with a stainless steel sheet with a diameter of 9 mm at both ends. It was pressurized at a pressure of 200 MPa or 350 MPa. The thickness of the electrolyte sheet was 1 mm. The AC impedance spectroscopy test was performed using the mold battery. The electrolyte impedance was measured by electrochemical impedance spectroscopy (EIS). On an electrochemical workstation (ChenHua, CHI630E), the impedance was measured by applying a direct current (DC) polarization voltage of 1 V, an amplitude of 50 mV, and a frequency range of 1 Hz~10 MHz. The ionic conductivity of the electrolyte material was calculated according to the following ionic conductivity formula. The specific formula is as follows:

[0084] Where σ is the ionic conductivity, unit is S·cm –1 ; L is the thickness of the electrolyte sheet, unit cm; R is the electrolyte resistance, unit ; S is the effective contact area between the stainless steel sheet and the electrolyte powder, unit: cm 2 .

[0085] X-ray powder diffraction test

[0086] The crystal structure of the sample was analyzed using X-ray powder diffraction (XRD). A Bruker D8Advance diffractometer equipped with Cu Kα radiation (λ = 1.5406 Å) was used. The test parameters were set as follows: tube voltage of 40 kV, tube current of 40 mA, scan range of 2θ = 5°-90°, scan step size of 0.02°, and scan rate of 5° / min. The sample was uniformly dispersed in powder form on a glass slide with no diffraction background and compacted to minimize the effect of interparticle voids on the diffraction results.

[0087] XRD data were processed and analyzed using Jade software. First, the raw data was imported into the software for background subtraction and signal optimization. The peak search function automatically identified the diffraction peak locations, and a Gaussian function was selected for peak shape fitting. Parameters were adjusted to ensure that the fitted curve matched the experimental data. After fitting, the software directly outputs the peak area I and half-maximum width x of the diffraction peak. The half-maximum width represents the width at half the peak height, and the peak area represents the integrated area of ​​the diffraction peak, expressed in degrees (°).

[0088] Example 1-1

[0089] Li2S, P2S5 and LiCl were crushed separately using Tianchuang Powder QXQM-6 ball mill. After crushing, the D50 of Li2S was 6.1μm, the D50 of P2S5 was 6.5μm, and the D50 of LiCl was 6.6μm.

[0090] In an Ar atmosphere, Li2S, P2S5, and LiCl were weighed as substrates in a molar ratio of 5:1:2. 1 kg of the substrates corresponded to 0.5 L of n-hexane (substrate: solvent mass ratio = 3:1). The mixture was stirred at 500 rpm for 30 min at room temperature and atmospheric pressure to obtain a viscous solid mixture.

[0091] The mixture was placed in an Ar atmosphere at room temperature and normal pressure overnight to evaporate the solvent. The solvent evaporation rate was controlled at 5 mg / cm 2 ·h, so that the residual solvent content is kept below 5wt%, and a solid electrolyte precursor mixture is obtained, whose X-ray diffraction pattern is as follows Figure 6 The volatilization rate is controlled by using a large watch glass at room temperature and pressure, so that the dry specific surface area per gram of sample is 1.51 cm 2 , the sample thickness is 2.2 mm.

[0092] The solid electrolyte precursor mixture was heated to 200°C at a heating rate of 3°C / min and heated for 3 hours to remove the residual organic solvent; then the temperature was further increased to 550°C at a heating rate of 7°C / min and heated for 10 hours. The sintered product was ground for 1 hour to obtain a sulfide solid electrolyte (Li6PS5Cl), whose X-ray diffraction pattern is as follows Figure 1 As shown, Figure 4 for Figure 1 The enlarged image of the diffraction peak corresponding to the (111) crystal plane, Figure 5 for Figure 1 A magnified image of the diffraction peak corresponding to the (311) crystal plane.

[0093] Example 1-2 to Example 1-3

[0094] Except for adjusting the type of LiX according to Table 1, the rest is the same as Example 1-1.

[0095] Example 1-4 to Example 1-5

[0096] Except for adjusting the molar ratio of the substrate according to Table 1, the rest is the same as Example 1-1. The X-ray diffraction pattern of the sulfide solid electrolyte of Example 1-4 is as follows: Figure 2 shown.

[0097] Examples 1-6

[0098] Except for adjusting the type of LiX and the molar ratio of the substrate according to Table 1, the rest is the same as Example 1-1.

[0099] Example 2-1 to Example 2-2

[0100] Except for adjusting the mass ratio of substrate to solvent according to Table 2, the rest is the same as Example 1-1.

[0101] Example 2-3 to Example 2-4

[0102] Except for adjusting the first sintering temperature according to Table 2, the rest is the same as Example 1-1.

[0103] Example 2-5 to Example 2-6

[0104] Except for adjusting the first sintering time according to Table 2, the rest is the same as Example 1-1.

[0105] Example 2-7 to Example 2-8

[0106] Except for adjusting the second sintering temperature according to Table 2, the rest is the same as Example 1-1. The X-ray diffraction pattern of the sulfide solid electrolyte of Example 2-7 is as follows: Figure 3 shown.

[0107] Example 2-9 to Example 2-10

[0108] Except for adjusting the second sintering time according to Table 2, the rest is the same as Example 1-1.

[0109] Example 3-1 to Example 3-4

[0110] Except for adjusting the D50 of the substrate according to Table 3, the rest is the same as Example 1-1.

[0111] Example 4-1 to Example 4-6

[0112] Except for adjusting the type of solvent according to Table 4, the rest is the same as Example 1-1.

[0113] Example 5-1 to Example 5-4

[0114] Except for adjusting the first sintering heating rate according to Table 5, the rest is the same as Example 1-1.

[0115] Example 5-5 to Example 5-8

[0116] Except for adjusting the second sintering heating rate according to Table 5, the rest is the same as Example 1-1.

[0117] Example 6-1 to Example 6-6

[0118] Except for adjusting the stirring time according to Table 6, the rest is the same as Example 1-1.

[0119] Example 7-1 to Example 7-2

[0120] Except for adjusting the post-processing method according to Table 7, the rest is the same as Example 1-1.

[0121] Example 8-1

[0122] In an inert atmosphere, Li6PS5Cl and Li2O prepared in Example 1-1 at a specific mass ratio (99.9:0.01) were weighed and transferred to a ball mill. 0.5 mm zirconium beads were added (ball-to-material ratio of 2:1). After sealing the ball mill, the mixture was ball milled at 500 rpm for 6 h in a Changsha Tianchuang powder planetary ball mill to obtain the sample Li6PS5Cl@0.01Li2O.

[0123] Example 8-2

[0124] Except for adjusting the coating oxide to SiO2 according to Table 9, the rest is the same as Example 8-1.

[0125] Comparative Example 2-1 to Comparative Example 2-2

[0126] Except for adjusting the mass ratio of substrate to solvent according to Table 2, the rest is the same as Example 1-1.

[0127] Comparative Examples 2-3

[0128] Except that the first sintering is not performed according to Table 2, the rest is the same as Example 1-1.

[0129] Comparative Example 2-4 to Comparative Example 2-5

[0130] Except for adjusting the first sintering temperature and time according to Table 2, the rest is the same as Example 1-1.

[0131] Comparative Example 2-6 to Comparative Example 2-7

[0132] Except for adjusting the second sintering temperature and time according to Table 2, the rest is the same as Example 1-1.

[0133] Comparative Examples 2-8

[0134] Except that no solvent was added according to Table 2, the rest was the same as Example 1-1.

[0135] Comparative Example 4-1 to Comparative Example 4-3

[0136] Except for adjusting the type of solvent according to Table 4, the rest is the same as Example 1-1.

[0137] Among them, when ethanol is used as a solvent, due to the strong interaction between the substrate and the ethanol solvent, the substrate dissolves and even forms a complex. Therefore, ethanol cannot be dried and subsequent experiments cannot be carried out. There is no relevant data.

[0138] Comparative Example 5-1

[0139] Example 2 in the publication of patent application CN115621538A was used as comparative example 5-1. The X-ray diffraction pattern of the electrolyte precursor powder is as follows: Figure 7 shown.

[0140] Comparative Example 5-2

[0141] The same method as in Example 1-1 was used except that the substrate and solvent were mixed by ball milling, wherein zirconium balls were used for ball milling, the ball-to-solvent ratio was 5:1, and the ball milling was carried out at a rotation speed of 300 rpm for 12 hours.

[0142] Comparative Example 5-3

[0143] The method was the same as that of Example 1-1 except that ultrasonic dispersion was used when mixing the substrate and the solvent, wherein the ultrasonic treatment frequency was 1 time / 2 hours, the ultrasonic power was 800 W, and the ultrasonic time was 5 minutes / time.

[0144] Comparative Example 5-4

[0145] The process was the same as that of Example 1-1, except that the suspension was vacuum dried at 60° C. for 24 h instead of being placed in an Ar atmosphere at room temperature and normal pressure overnight.

[0146] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Tables 1 to 9.

[0147] Table 1

[0148] Table 2

[0149] In Table 2, “ / ” indicates no relevant parameters.

[0150] Table 3

[0151] Table 4

[0152] In Table 4, “ / ” indicates no relevant parameters.

[0153] Table 5

[0154] Table 6

[0155] Table 7

[0156] Table 8

[0157] Table 9

[0158] As shown in Table 1, limiting the molar ratio of the substrate to the range of this application can avoid structural changes in the sulfide solid electrolyte material, which can lead to a decrease in ionic conductivity. As shown in Table 2, limiting the substrate to solvent mass ratio, the first sintering temperature and time, and the second sintering temperature and time within the range of this application can achieve higher ionic conductivity. When the second sintering temperature is below the range of this application, the substrate does not react completely, suitable crystal planes are not formed, and the I1 / I2 ratio is large, resulting in lower ionic conductivity. When the second sintering temperature is above the range of this application, the product LPSC undergoes side reactions, leading to the precipitation of LiX (e.g., LiCl), which reduces the I1 / I2 ratio, destroying the overall product structure and reducing ionic conductivity. As shown in Table 3, controlling the substrate D50 within the range of this application promotes uniform diffusion of the reaction and distribution of crystal nuclei, thereby providing a good foundation for directional crystal growth. The I1 / I2 ratio is within the range of this application, thereby improving the ionic conductivity of the sulfide solid electrolyte. As can be seen from Table 4, the solvent type is within the scope of this application, which can effectively prevent hydrolysis of the precursor and reduce the content of oxygen impurities (such as Li3PO4) in the sulfide solid electrolyte, thereby further improving the ionic conductivity of the sulfide solid electrolyte. As can be seen from Table 5, the heating rate of the two sintering processes is within the scope of this application, which can ensure that the volatilization of the solvent does not introduce excessive voids in the sulfide solid electrolyte, and the crystal structure of the sulfide solid electrolyte is intact, with high ionic conductivity. As can be seen from Table 6, when the mechanical stirring is controlled at room temperature and pressure and the stirring speed is within the scope of this application, the substrates do not react with each other when mixing with the solvent, and a sulfide solid electrolyte with high ionic conductivity can be obtained. When the stirring time is controlled within the scope of this application, the substrates can be more fully contacted, thereby obtaining a sulfide solid electrolyte with higher ionic conductivity. As can be seen from Table 7, the post-treatment method of this application achieves high ionic conductivity. As can be seen from Table 8, when the solvent is dried by standing at room temperature and pressure as described in the present application and the substrate and solvent are mixed by stirring as described in the present application, the sulfide solid electrolyte obtained has low porosity and high ionic conductivity. When the substrate and solvent are mixed by ultrasonic dispersion or ball milling, the substrate partially reacts during mixing, resulting in an increase in the porosity of the sulfide solid electrolyte and a decrease in the ionic conductivity. When the solvent is dried by vacuum drying, the porosity of the sulfide solid electrolyte increases more significantly and the ionic conductivity of the sulfide solid electrolyte decreases. When the substrate and solvent are mixed by ultrasonic dispersion and vacuum drying, the porosity of the sulfide solid electrolyte obtained increases further and the ionic conductivity decreases further. As can be seen from Table 9, the surface of the sulfide solid electrolyte prepared in the present application is coated with an inert oxide layer, and its conductivity does not decrease significantly, but the addition of the oxide layer can well isolate the sulfide from contact with moisture in the air. Figure 6 and Figure 7It can be seen that in Example 1-1, only the characteristic peaks of the substrate lithium sulfide and lithium chloride (phosphorus pentasulfide is an amorphous structure, and the diffraction peak intensity in XRD is extremely low and masked) are shown, while in Comparative Example 5-1, the relative intensity of the substrate lithium sulfide and lithium chloride peaks decreases, and the relative intensity of the intermediate Li3PS4 and the product LPSC increases, indicating that the reaction between the substrates has occurred at this time. Therefore, the mechanism of the patent application CN115621538A is completely different from the mechanism of this application. In addition, from Figures 1 to 3 It can be seen that the substrate ratio and the second sintering temperature will affect the ratio of I1 / I2 of the sulfide solid electrolyte. Figure 4 and Figure 5 It can be seen that the half-peak width x1 of the (111) crystal plane of the sulfide solid electrolyte prepared in Example 1-1 is 0.137, and the half-peak width x2 of the (311) crystal plane is 0.146.

[0159] In addition, since the role of the first sintering is only to dry the solvent, the substrate begins to react to form a sulfide solid electrolyte during the second sintering. Therefore, the first sintering temperature and time have little effect on the value of I1 / I2. Combining Example 2-3, Example 2-4 and Comparative Examples 2-3 to Comparative Examples 2-5, it can be seen that regardless of whether the first sintering temperature and time are within the scope of this application, the value of I1 / I2 changes little, which mainly affects the volatilization of the solvent. When the temperature of the first sintering is too low or the time is too short, the solvent evaporates incompletely, which ultimately leads to a decrease in the ionic conductivity of the sulfide solid electrolyte.

[0160] In summary, the sulfide solid electrolyte of the present application has high ionic conductivity. Specifically, the I1 / I2 ratio of the sulfide solid electrolyte is within the scope of the present application, i.e., the relative ratio of the main crystal plane (111) to the crystal plane (311) is moderate, which can optimize the crystal orientation, effectively improve the lithium ion migration path within the material, and help maintain the mechanical strength and sintering density of the material. This improves the ionic conductivity while ensuring the structural stability of the sulfide solid electrolyte. Furthermore, the preparation method of the present application controls the D50 of the substrate within the range of the present application, which is conducive to the uniform diffusion of the reaction and the distribution of crystal nuclei, thereby providing a good foundation for the directional growth of crystals, thereby improving the ionic conductivity of the sulfide solid electrolyte; the use of low-polarity, inert alkane solvents can inhibit the directional complexation reaction between the substrates, which is conducive to the preferential growth of the (111) crystal plane; the mass ratio of the solvent to the substrate is controlled within the range of the present application, and the substrate particles are more evenly dispersed, which helps to control the nucleation position, thereby affecting the direction of crystal growth; however, excessive use can easily lead to disordered crystal plane structure; by controlling the sintering temperature and time, the ionic conductivity and phase purity of the electrolyte are improved, and the overall performance of the electrolyte is also enhanced. Furthermore, batteries containing the sulfide solid electrolyte of the present application or the sulfide solid electrolyte prepared by the preparation method of the present application have high safety and energy density as well as good low-temperature performance, and can be used in electric vertical take-off and landing aircraft, such as low-altitude economic manned electric vertical take-off and landing aircraft.

[0161] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A sulfide solid electrolyte, characterized in that: The chemical formula of the sulfide solid electrolyte is Li 7-a PS 6- a X a , X is a halogen, 1≤a≤2; wherein, the peak area of ​​the diffraction peak corresponding to the (111) crystal plane of the sulfide solid electrolyte is I1, the peak area of ​​the diffraction peak corresponding to the (311) crystal plane of the sulfide solid electrolyte is I2, and I1 and I2 satisfy: 0.2≤I1 / I2≤0.

3.

2. The sulfide solid electrolyte according to claim 1, characterized in that The half-maximum width of the diffraction peak corresponding to the (111) crystal plane of the sulfide solid electrolyte is x1, and the half-maximum width of the diffraction peak corresponding to the (311) crystal plane of the sulfide solid electrolyte is x2. x1 and x2 satisfy: 0.12<x1<0.2, 0.14<x2<0.

22.

3. The sulfide solid electrolyte according to claim 1, characterized in that The particle size of the sulfide solid electrolyte satisfies: 0.5µm<D50<1µm, 1.4µm<D90<2µm, 10µm<D MAX <15µm.

4. The sulfide solid electrolyte according to claim 1, characterized in that The ionic conductivity of the sulfide solid electrolyte is ≥5.3 mS / cm.

5. The sulfide solid electrolyte according to claim 1, characterized in that The sulfide solid electrolyte also includes at least one of O, Se, F, Mg, Ca, Sr, Zn, Sc, Sb, Si, Ge, Sn, B, Al, Ga, In, Ti, Zr, V, Nb, Cu, Ni, Mn, Cr, Ag, La, Ce, Tb, Te, Pb, As, Bi, Fe, Mo, Hf, Y and Ru elements, and the elements are introduced by doping or coating.

6. The sulfide solid electrolyte according to claim 1, characterized in that The surface of the sulfide solid electrolyte is coated with an inert oxide layer, and the inert oxide layer is selected from at least one of Li2O, Al2O3, V2O5, ZnO, ZrO2, TiO2, MgO, RuO2, La2O3, CeO2, HfO2, Y2O3, SiO2, B2O3, CuO, NbO2, LiNbO3, and LiAlO2.

7. A method for preparing a sulfide solid electrolyte according to any one of claims 1 to 4, characterized in that: Under inert atmosphere protection, a substrate and a solvent are mixed and mechanically stirred to obtain a solid mixture; wherein the substrate comprises Li2S, P2S5, and LiX, where X is a halogen; before mixing the substrate and the solvent, the substrate and the solvent are respectively crushed to 3 μm ≤ D50 ≤ 10 μm; the molar ratio of the Li2S to the P2S5 is (3-5):1; the molar ratio of the P2S5 to the LiX is 1:(2-4); and the mass ratio of the solvent to the substrate is 1:(1.5-3); The solid mixture is allowed to stand at room temperature and pressure to evaporate the solvent, thereby obtaining a solid electrolyte precursor mixture; The solid electrolyte precursor mixture is sintered to obtain a sulfide solid electrolyte; wherein the sintering includes a first sintering and a second sintering, the temperature of the first sintering is 150~300℃, and the time is 1~6h; the temperature of the second sintering is 450~600℃, and the time is 10~15h.

8. The preparation method according to claim 7, characterized in that Before mixing the substrate with the solvent, the substrate is crushed to 5µm≤D50≤8µm.

9. The preparation method according to claim 7, characterized in that The temperature of the first sintering is 200-300° C., and the time is 3-6 hours; the temperature of the second sintering is 550-600° C., and the time is 10-13 hours.

10. The preparation method according to claim 7, wherein The heating rate of the first sintering is 2-5°C / min; the heating rate of the second sintering is 5-10°C / min.

11. The preparation method according to claim 7, characterized in that The solvent is selected from at least one of n-hexane, benzene, toluene, cyclohexane, n-pentane, cyclopentane and dimethyl carbonate.

12. The preparation method according to claim 7, characterized in that The mechanical stirring is carried out at room temperature and pressure, the rotation speed of the mechanical stirring is 300 rpm to 600 rpm, and the time of the mechanical stirring is 10 to 50 minutes.

13. The preparation method according to claim 7, characterized in that The solvent evaporation rate is 1.5~7.0 mg / cm 2 ·h.

14. The preparation method according to claim 7, characterized in that After the sintering, post-processing is required, and the post-processing includes crushing. 15 . A battery comprising a positive electrode sheet, a negative electrode sheet, and the sulfide solid electrolyte according to claim 1 .

16. Use of the battery according to claim 15 in an electric vertical take-off and landing aircraft.

Citation Information

Patent Citations

  • Small-particle-size sulfide solid electrolyte and preparation method thereof

    CN115621538A

  • Sulfide solid electrolyte

    CN109937507A

  • Sulfide and preparation method thereof, solid electrolyte, all-solid-state battery and electric equipment

    CN117594869A

  • Sulfide solid electrolyte and preparation method and application thereof

    CN120048987A

  • Method for Wet Chemical Synthesis of Lithium Argyrodites

    US20220227624A1

Cited By

  • Solid electrolyte with multi-layer coating structure, preparation method of solid electrolyte and battery

    CN122073253A

  • Solid electrolyte of multilayered coating structure, method for preparing solid electrolyte, and battery

    CN122073253B